1985
DOI: 10.1073/pnas.82.9.2784
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of human malaria parasites to chloroquine is pH dependent.

Abstract: Chloroquine (CQ) accumulates in the acidic food vacuole of intraerythrocytic malaria parasites (Plasmodium falciparum) by virtue of its weak base properties. In the present work, the extent of CQ accumulation was determined by the transvacuolar pH gradient: modification of the lattereither by changing the external pH or by adding the acidotropic agent NH4Cl-led to a corresponding change in CQ distribution between cells and medium. Changes in pH gradient provoked a change in the susceptibility of parasites to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 32 publications
4
105
0
1
Order By: Relevance
“…The mechanism(s) underlying resistance to the widely used quinoline-containing drugs remains strongly debated. The antimalarial property of this group of drugs (exemplified by CQ) is believed to be mediated by accumulation/trapping in the acidic food vacuole of the parasite (3,4) and inhibition of polymerization of toxic heme groups generated by degradation of the host hemoglobin (5). Resistance seems pleiotropic as in vivo (6,7) and in vitro (8,9) cross-resistance of MFQ, HA, and QI (but generally not CQ) has been observed.…”
mentioning
confidence: 99%
“…The mechanism(s) underlying resistance to the widely used quinoline-containing drugs remains strongly debated. The antimalarial property of this group of drugs (exemplified by CQ) is believed to be mediated by accumulation/trapping in the acidic food vacuole of the parasite (3,4) and inhibition of polymerization of toxic heme groups generated by degradation of the host hemoglobin (5). Resistance seems pleiotropic as in vivo (6,7) and in vitro (8,9) cross-resistance of MFQ, HA, and QI (but generally not CQ) has been observed.…”
mentioning
confidence: 99%
“…23 Chloroquine may interfere with hemoglobin degradation in the food vacuole by raising the vacuolar pH. 24 It was postulated that chloroquine and quinine inhibited hematin polymerization in the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…Previous attempts to measure the pH of the parasite digestive vacuole using the diprotic weak base CQ (Bray et al, 1992;Geary et al, 1990;Geary et al, 1986;Yayon et al, 1984;Yayon et al, 1985) as a probe have proved problematic. Some studies suggested that CQ accumulation by the parasite could be fully accounted for by the diffusion of the uncharged form of the molecule across the various membranes separating the interior of the digestive vacuole from the extracellular medium, with the protonated form accumulating in each compartment in accordance with the Henderson-Hasselbach equation and pH DV~4 .2-4.5 (Geary et al, 1990;Geary et al, 1986;Ginsburg et al, 1989;Hawley et al, 1996;Yayon et al, 1985). However, other studies suggested that some parasites accumulated much more CQ than could be predicted by this model (Krogstad et al, 1992;Krogstad and Schlesinger, 1986;Krogstad and Schlesinger, 1987;Krogstad et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that an increased pH DV in CQR parasites will result in a reduction in the trapping of CQ in the vacuole (Ferrari and Cutler, 1991;Homewood et al,compatible with the reduction in the apparent haematin binding affinity observed in CQR parasites . Several studies have demonstrated that increasing extracellular pH results in an increase in CQ uptake (Bray et al, 1994;Geary et al, 1990;Hawley et al, 1996;Yayon et al, 1985), an increase in CQ sensitivity of the parasites (Geary et al, 1990;Martiney et al, 1995;Yayon et al, 1985) and an increase in the apparent affinity of CQ-haematin binding . These observations are consistent with the hypothesis that CQ accumulation is a function of transmembrane pH gradients, although the variation in CQ uptake with extracellular pH could also be a result of the pH dependence of the concentration of the membrane-permeant neutral form of the molecule in the external medium, and consequent changes in the concentration and hence extent of binding of the drug in subcellular compartments.…”
Section: Introductionmentioning
confidence: 99%